Prognostic factors of premature closure of the ductus arteriosus in utero: a systematic literature review. (20th June 2016) - Ishida, Hidekazu; Kawazu, Yukiko; Kayatani, Futoshi; Inamura, Noboru
Abstract: Background: A number of case reports show various outcomes of premature closure of the ductus arteriosus in utero, including persistent pulmonary hypertension of the newborn and fetal or neonatal death; however, no study clarifies the clinical observations that are related to their prognoses. We aimed to clarify the prognostic factors of intrauterine ductal closure by a systematic literature review. Data sources: We searched PubMed database (1975–2014) to identify case reports and studies on intrauterine closure of the ductus arteriosus, including maternal, fetal, and neonatal clinical information and their prognoses. Results: We analysed the data of 116 patients from 39 articles. Of these, 12 (10.3%) died after birth or in utero. Fetal or neonatal death was significantly correlated with fetal hydrops (odds ratio=39.6, 95% confidence interval=4.6–47.8) and complete closure of the ductus arteriosus (odds ratio=5.5, 95% confidence interval=1.2–15.1). Persistent pulmonary hypertension was observed in 33 cases (28.4%), and was also correlated with fetal hydrops (odds ratio=4.2, 95% confidence interval=1.3–4.6) and complete closure of the ductus arteriosus (odds ratio=5.5, 95% confidence interval=1.6–6.0). Interestingly, maternal drug administration was not correlated with the risk of death and persistent pulmonary hypertension. Conclusions: Fetal hydrops and complete ductal closure are significant risk factors for both death and persistent pulmonary hypertension. Cardiac or neurological prognoses could be favourable if the patients overcome right heart failure during the perinatal period.